A response–surface–based tool for vehicle front–end design for pedestrian impact protection using human body model. (3rd December 2014) - Nie, Bingbing; Xia, Yong; Zhou, Qing; Huang, Jun; Deng, Bing; Neal, Mark
This study introduces a response–surface–based design tool of vehicle front–end for pedestrian lower limb impact protection performance. Using a simplified parametric vehicle front–end model, a pedestrian human body model (HBM) and impact simulations, a design of experiment (DOE) study is conducted, and based on the results, response surfaces for lower limb injury predictions have been generated. The Latin Hypercube sampling scheme is used to create the models of the front structure of a variety of vehicles, and reasonable geometry and stiffness variables are included. The response surfaces have been implemented in a graphical user interface (GUI) to provide simple and intuitive feedback on human lower limb injury predictions as the vehicle front–end design changes.